KONSEP KORUPSI MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Ahmad Syarbaini (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2022)
Corruption comes from the Latin coruptio and corruptuswhich means to bribe and corrumpere which means todestroy. Corruption is included in jarîmah. Jarîmah is:"Prohibitions of syara', namely; Threats with 'uqūbat hador ta'zir". Ta'zir is: "'uqūbat determined by theauthorities in order to refuse thinning and preventcrime". Corruption in Indonesian law is: "Unlawfullycommitting acts of enriching oneself or another person ora corporation that can harm state finances or the stateeconomy". While the terms that are close to corruption inIslamic studies are: "ghulūl, ikhtilâs, risywah and alfasadand". Corruption according to fiqh is: "It is ajarîmah or a modern and extraordinary crime for whichthere is no agreement on the terms and definitions. Whilethe 'uqūbat is ta'zîr which is returned to waliyul amri".